THE EFFECT OF PROVIDING EDUCATION ON HEALTHY MENU PREPARATION ON MOTHERS' KNOWLEDGE IMPROVEMENT AND CHILDREN'S WEIGHT GAIN CHART INCREASE - Ritawati Ritawati; Eka Okta Riani (Universitas Bina Bangsa Getsempena, 2023)
In 2022, it was estimated that 45 million children under the age of 5 (6.8%) suffered from wasting, with 13.6 million (2.1%) of them experiencing severe wasting. More than three-quarters of children with severe wasting live in Asia, and 22% live in Africa. The 2023 Joint Malnutrition Estimates (JME) report showed insufficient progress toward meeting the global nutrition targets set by WHO for 2025 and the Sustainable Development Goals (SDGs) for 2030. The aim of this study is to investigate the impact of providing education on healthy menu preparation on improving mothers' knowledge and children's weight gain in Tibang Village, Syiah Kuala District, Banda Aceh City. This study is a “Quasi-experimental pre-post test” design, where an intervention or treatment is given to the study subjects, and the effects of the treatment are then measured and analyzed. The population in this study consisted of all mothers with children aged 1-5 years in Tibang Village, Syiah Kuala District, Banda Aceh City at the time of the study, with a sample size of 95 participants selected through total sampling. The study was conducted in June 2023 using observation sheets for data collection. Data analysis was performed using the Wilcoxon test. The univariate analysis results show that before receiving the education on healthy menu preparation, the majority of mothers (52.6%) had insufficient knowledge, whereas after receiving the education, most mothers (57.9%) had good knowledge. Regarding children's weight, before the education, 63.2% of children did not show weight gain, whereas after the education, 68.4% of children showed weight improvement. The bivariate analysis results indicate that there was a significant effect of providing education on healthy menu preparation on improving mothers' knowledge, with a p-value of 0.000 < α: 0.05, and also a significant effect on children's weight gain, with a p-value of 0.001 < α: 0.05. It is hoped that mothers can increase their knowledge about healthy menu preparation for children aged 1-5 years.